Phytochemicals in leaves and roots of selected Kenyan orange fleshed sweet potato (OFSP) varieties - Abong, G.O.; Muzhingi, T.; Okoth, M.W.; Ng'ang'a, F.; Ochieng’, P.E.; Mbogo, D.; Malavi, D.N.; Akhwale, M.; Ghimire, S. (Hindawi Limited, 2020)
This study reports the inherent phytochemical contents in leaves and roots of nine sweet potato varieties from Kenya. Results indicated that vitamin C content varied significantly () among the sweet potato varieties regardless of the plant part, leaves having significantly () higher levels than in the roots. Total flavonoids and phenolic compounds differed significantly () among varieties, higher values were found in leaves than in roots. Flavonoid contents in roots ranged from below detectable limits (Whitesp) to 25.8 mg CE/100 g (SPK031), while in leaves it ranged from 4097 to 7316 mg CE/100 g in SPK4 and Kenspot 5, respectively. Phenolic content was below detectable limits in the roots of whitesp but it was in substantial amounts in orange fleshed varieties. The β-carotene content was significantly () higher in leaves (16.43–34.47 mg/100 g dry weight) than in roots (not detected—11.1 mg/100 g dry weight). Total and phytic phosphorus were directly correlated with phytate contents in leaves and the roots. Tannins and soluble oxalates varied significantly () with variety and plant part being higher in leaves. The current information is important for ration formulations and dietary recommendations utilizing sweet potato leaves and roots. Future studies on effects of processing methods on these phytochemicals are recommended.